2020
DOI: 10.1029/2019ja027483
|View full text |Cite
|
Sign up to set email alerts
|

The Properties and Origins of Corotating Plasmaspheric Irregularities as Revealed Through a New Tomographic Technique

Abstract: This paper describes insights into the nature of corotating plasmaspheric irregularities (CPIs) enabled by a newly developed method for range-and time-resolved tomographic images of these structures. The method is based on high-precision measurements of total electron content gradients measure toward cosmic radio sources using an interferometric radio telescope, the Very Large Array (VLA). Exploiting hundreds of hours of data from the VLA Low-band Ionosphere and Transient Experiment, we confirm that CPIs are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(45 citation statements)
references
References 50 publications
7
38
0
Order By: Relevance
“…This may indicate that the polarization electric fields that are the hallmarks of electrobuoyancy waves can also play a role in driving the formation of disturbed flux tubes in the upper ionosphere/lower plasmasphere. In fact, a long‐term study of corotating plasmaspheric irregularities by Helmboldt et al (2020) has shown that this is likely the case, at least over North America. If the same phenomenon is active here, it could be that some of the disturbed flux tubes/ducts observed with MWA are driven by ionospheric electric field perturbations that occurred too far south to be directly imaged with MWA, but whose effects were seen within the topside ionosphere/lower plasmasphere over the telescope.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…This may indicate that the polarization electric fields that are the hallmarks of electrobuoyancy waves can also play a role in driving the formation of disturbed flux tubes in the upper ionosphere/lower plasmasphere. In fact, a long‐term study of corotating plasmaspheric irregularities by Helmboldt et al (2020) has shown that this is likely the case, at least over North America. If the same phenomenon is active here, it could be that some of the disturbed flux tubes/ducts observed with MWA are driven by ionospheric electric field perturbations that occurred too far south to be directly imaged with MWA, but whose effects were seen within the topside ionosphere/lower plasmasphere over the telescope.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…While the CPI data provide good constraints on λ , V ph must be assumed. A phase speed of 20 m s −1 was assumed for similar calculations by Helmboldt et al (2020) and Helmboldt (2020) because it yielded simulated data with properties similar to those actually observed, and the same was the case for this study.…”
Section: Discussionmentioning
confidence: 54%
“…These are roughly consistent with the properties of the waves noted within SuperDARN data by Ogawa et al (2009). This is significantly larger than the apparent wavelengths typically measured for CPIs of 20–50 km (Helmboldt, 2020; Helmboldt et al, 2020). However, the beam spacing of the radars is such that only phase fronts with wavelengths >70 km can be resolved out to the maximum E region range of 630 km.…”
Section: Observationsmentioning
confidence: 62%
See 2 more Smart Citations